Effect of plasma aldosterone concentration on serum uric acid metabolism - WEI Yushuang; LI Mingli; XU Mingjie; YAN Boteng; JIN Xihui; MAI Xiaoyou; WU Yongxian; HUANG Shengzhu; MO Zengnan (Guangxi Yike Daxue xuebao)
Objective To explore the associations between primary aldosteronism (PA)-related phenotypes and serum uric acid (SUA) levels as well as the risk of hyperuricemia. Methods A total of 1, 986 high-risk individuals for PA were selected from those screened at two medical centers in Nanning and Yulin, Guangxi, China between October 2022 and February 2024. Based on a cross-sectional observational design, multivariable linear regression, binary logistic regression, and restricted cubic spline (RCS) analyses were used to assess the associations between plasma aldosterone concentration (PAC), plasma renin concentration (PRC), and PA with SUA levels and the risk of hyperuricemia. Results Multiple linear regression analysis showed a positive correlation between PAC and SUA levels (β=0.064, 95% CI: 0.039-0.090, P < 0.001), whereas the correlation between PRC and SUA levels was not statistically significant. Multivariable binary logistic regression analysis indicated that PAC was a risk factor for hyperuricemia. Specifically, compared with the first quartile (Q1 group), the risk of hyperuricemia in the third quartile (Q3 group) and the fourth quartile (Q4 group) of PAC was 1.390 times and 1.717 times higher, respectively. PA was an independent risk factor for hyperuricemia (OR=1.647, 95% CI: 1.172-2.313, P=0.004). RCS analysis showed a linear dose-response relationship between PAC and SUA levels (Poverall < 0.001, Pnonlinear=0.192) and the risk of hyperuricemia (Poverall=0.002, Pnonlinear=0.192). Conclusion PAC is positively correlated with SUA and hyperuricemia, suggesting that proper control of circulating aldosterone levels is helpful to prevent disorders of uric acid metabolism.